2014
DOI: 10.1016/j.coph.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Brain neuropeptides in gastric mucosal protection

Abstract: The centrally induced gastroprotective effect of neuropeptides has been intensively studied. Besides many similarities, however, differences can also be observed in their gastroprotective actions. The gastroprotective dose-response curve proved to be either sigmoid, or bell-shaped. Additional gastrointestinal effects of neuropeptides can contribute to their mucosal protective effect. Part of the neuropeptides induce gastroprotection by peripheral administration as well. Besides vagal nerve the sympathetic nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…They injected the 14-amino acid neuropeptide bombesin into the cisterna magna and noted the changes in the autonomic nervous system activity, resulting in the simultaneous inhibition of gastric acid and pepsin secretion and motility [42]. In future decades the involvement of neuropeptides in the regulation of the function of gut was confirmed by numerous papers of other authors [6,28,29,41,38,39,43]. Thus, it was shown that opioid peptides, the most numerous family of neuropeptides, have much broader physiological effects than the regulation of emotions.…”
Section: Neuropeptidesmentioning
confidence: 57%
See 3 more Smart Citations
“…They injected the 14-amino acid neuropeptide bombesin into the cisterna magna and noted the changes in the autonomic nervous system activity, resulting in the simultaneous inhibition of gastric acid and pepsin secretion and motility [42]. In future decades the involvement of neuropeptides in the regulation of the function of gut was confirmed by numerous papers of other authors [6,28,29,41,38,39,43]. Thus, it was shown that opioid peptides, the most numerous family of neuropeptides, have much broader physiological effects than the regulation of emotions.…”
Section: Neuropeptidesmentioning
confidence: 57%
“…Due to the recent literary data, the most explored representatives of oligopeptides with gastroprotective properties are met-enkephaline (His-D-Trp-Ala-Trp-D-Phe-Lys-NH2) [27,28] and leu-enkephaline (Tyr-Gly-Gly-Phe-Leu) [27][28][29], demorphine (Н-Tyr-D-Ala-Phe-Gly-Tyr-Pro-Ser-NH 2 ) and sedatine (H-ArgTyr-D-Ala-Phe-Gly-OH) [5,30], pentadecapeptide BPC 157 (GlyGlu-Pro-Pro-Pro-Gly-Lys-Pro-Ala-Asp-Asp-Ala-Gly-Leu-Val) [10,[31][32][33]; proline-and hydroxyproline-containing products…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…amylin, adrenomedullin, neurotensin, opioid peptides, melatonin, ghrelin, leptin, as well as cannabinoids were shown to initiate gastroprotective effect given centrally (i.c.v., i.c. or DMNV), mostly by a vagal dependent mechanism [139][140][141][142] (see reviews: [4,127,138,143,144]). …”
Section: Role Of Capsaicin Sensitive Afferent Fibers and In The Actiomentioning
confidence: 99%